Utilization of pineapple (Anonas Comosus Linn.) and papaya (Carica Papaya Linn.) fruit wastes in quick vinegar production - Yonzaga, Liza Q.
Vinegar was produced by the quick or generator method of acetic acid fermentation from the combined juices of pineapple and papaya trimmings, peels and culls. The pineapple and papaya juices were characterized as having average sugar contents and pH values of 14.4°Bx and 9.3°Bx and pH 3.68 and pH 4.72, respectively. A pineapple-to-papaya juice ratio of 2:1 was selected as most suitable for fermentation over two other ratios studied namely, 1:1 and 1:2. The selected juice mixture showed the highest sugar content (13.7°Bx) before fermentation, a favorable pH (3.79) and an adequate amount of alcohol for acetic acid production (10.1%) after alcoholic fermentation. The pineapple-papaya vinegar produced from the most desirable pineapple-papaya juice mixture using a laboratory generator was objectively analyzed and found to possess 3.27% total acids (expressed as acetic acid), 0.58% non-volatile acids and 2.69% volatile acids. A sensory panel described the pineapple-papaya vinegar as having a yellow to brownish yellow color, a slightly acidic odor, a slightly sour to sour flavor and a general acceptability rating corresponding to neither like nor dislike. In comparison descriptions for the commercial pineapple vinegar (evaluated simultaneously with pineapple-papaya vinegar) were given as having a brownish yellow color, an acidic odor, a very sour flavor and a general acceptability rating corresponding to like moderately. Using the T-test at the 5% level of significance, difference in terms of odor, flavor and general acceptability were detected between the pineapple-papaya vinegar and the commercial vinegar. No significant difference was found in the color of the two vinegar products.